2005
DOI: 10.1001/jama.293.2.183
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of Vegetables and Fruits and Risk of Breast Cancer

Abstract: ContextThe intake of vegetables and fruits has been thought to protect against breast cancer. Most of the evidence comes from case-control studies, but a recent pooled analysis of the relatively few published cohort studies suggests no significantly reduced breast cancer risk is associated with vegetable and fruit consumption.Objective To examine the relation between total and specific vegetable and fruit intake and the incidence of breast cancer. Design, Setting, and ParticipantsProspective study of 285 526 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
91
2
4

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 236 publications
(101 citation statements)
references
References 24 publications
4
91
2
4
Order By: Relevance
“…However, in the United Kingdom, the Chief Medical Officer's Committee on Medical Aspects of Food and Nutrition Policy (COMA) concluded that the effect was moderately consistent for vegetables but presented weak consistency for fruits 26 . In a cohort study published recently, van Gils et al 30 did not find any association between fruit and vegetables and breast cancer. However, they did not rule out the possibility of a protective effect by specific types of fruits and vegetables.…”
Section: Discussionmentioning
confidence: 89%
“…However, in the United Kingdom, the Chief Medical Officer's Committee on Medical Aspects of Food and Nutrition Policy (COMA) concluded that the effect was moderately consistent for vegetables but presented weak consistency for fruits 26 . In a cohort study published recently, van Gils et al 30 did not find any association between fruit and vegetables and breast cancer. However, they did not rule out the possibility of a protective effect by specific types of fruits and vegetables.…”
Section: Discussionmentioning
confidence: 89%
“…Other studies have also found no associations between different dietary patterns and risk of breast cancer. The EPIC cohort explored risk of breast cancer with fruit and vegetable consumption and found no associations (21), in that example however, the whole diet was not considered. This may be important, since another analysis of the EPIC data found that although adherence to the traditional Mediterranean diet was associated with a significant reduction in total mortality, the associations between each individual food group contributing to the Mediterranean-diet score and total mortality were not all individually significant (22).…”
Section: Discussionmentioning
confidence: 99%
“…The calibration method used has been previously described. 22,26,27 Briefly, the food item specific 24-hr diet recall values were regressed on the respective dietary questionnaire values, stratified by sex. Center-specific regression calibration models were used to correct for bias mainly attributable to differences in the dietary assessment instruments among EPIC centers.…”
Section: Statistical Analysesmentioning
confidence: 99%